Evaluation of treatment strategies for patients with stage IIIA non-small cell lung cancer in the immunotherapy era - Amy Alabaster; Jeffrey B. Velotta; Haley I. Tupper; Mark S. Walker; Yanina Natanzon (Cancer Treatment and Research Communications)
Background: Optimal treatment for patients with stage IIIA NSCLC is controversial. Growing evidence indicates surgery with adjuvant or neoadjuvant chemotherapy (SC) may be superior to non-surgical treatments. Direct comparisons have not been performed between SC and chemoradiation with immunotherapy (CRI) among patients diagnosed with stage IIIA NSCLC since consolidation immunotherapy was added to treatment guidelines. Methods: This retrospective study compared surgical and systemic non-surgical treatments (except targeted therapy) among adults diagnosed with stage IIIA NSCLC 2017–2021. Data was from ConcertAI's curated EHR Patient360™ NSCLC real-world care product. Real-world progression-free survival (rwPFS) and overall survival (rwOS) were evaluated among patients treated with SC or CRI using Kaplan-Meier and Cox proportional hazard methods. Baseline differences were balanced using propensity score-derived inverse probability treatment weights (IPTW). Results: Among 1718 eligible, the two main comparator groups (SC and CRI) had 431 (25%) and 576 (34%) patients; 711 patients received chemoradiation or monotherapy. A wide range of treatment strategies was observed across included oncology clinics (e.g., 0–67% clinic patients received surgery). IPTW-adjusted analyses showed reduced hazards in the SC group vs. CRI for rwPFS (HR 0.78, 95% CI: 0.63–0.97) and rwOS (HR 0.63, 95% CI: 0.49–0.82). SC was similarly beneficial for patients across nodal status groups and appeared especially beneficial for patients with resectable squamous-cell tumors. Conclusion: Stage IIIA NSCLC treatment is highly variable. Real-world studies can provide valuable evidence to support surgery as a treatment option for stage IIIA patients, who currently may only be offered chemoradiation with or without immunotherapy.